STRATUP BISNIS “KEJAM” : PELUANG DAN TANTANGAN - Restiana, Riska (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2016)
Business culinary is a prospective business and never die because everyone definitely need food as long as they still alive. These conditions cause innovations of processed foods that more and more. One of them is innovation of oyster mushroom. Oyster mushroom have a good taste and delicious and also rich nutrition that give many health benefits, other benefits of oyster mushroom are easy to get and the price is classified cheap. In this case the research object is business "KEJAM" (creations oyster mushroom). This research purpose are to know opportunities and challenges in starting a business "KEJAM" to be able to know anything that can push and prevent this business. Research methods used is qualitative methods with fenomenologic technique. Data was colected from direct observation and interview with consumers and prospective customers. Result of this study concluded that the opportunity of business "KEJAM" is huge because not a lot of competitors in the same business. While the challenges faced is difficult to get mushrooms with low price in dry season, consumers are easier bored with the same foods, increase of materials supporting price and consumer tend to choose fast food in the mall and grant shops. From the study is expected to be found a solution to resolve the challenges faced in the run business "KEJAM".